Awesome experiments in light & sound - Dispezio, Michael A.; Leary, Catherine (New York : Sterling, 1999)
Presents over seventy experiments designed to demonstrate the properties of light and sound and explain the science behind them, covering such topics as wavelengths, color spectrums, vibration, and air particles.
Includes index.
School Library Journal.
Science and Children (N.S.T.A.).
3.8
3-6
Keywords: Light -- Experiments -- Juvenile literature; Sound -- Experiments -- Juvenile literature; Experiments; Light -- Experiments; Sound -- Experiments; Experiments; Light -- Experiments; Sound -- Experiments